2019
DOI: 10.1186/s12909-018-1445-2
|View full text |Cite
|
Sign up to set email alerts
|

Willingness, concerns, incentives and acceptable remuneration regarding an involvement in teaching undergraduates - a cross-sectional questionnaire survey among German GPs

Abstract: BackgroundWorldwide, many undergraduate general practice curricula include community-based courses at general practitioners’ (GPs’) offices. Usually the academic general practice departments collaborate with networks of affiliated teaching practices. To successfully master the challenge of network development and extension, more information is needed about GPs’ willingness to be involved in different teaching formats, important influencing factors, incentives, barriers, and the need for financial compensation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
1
11
1
2
Order By: Relevance
“…Previous work on the engagement of rural and distributed faculty has emphasized the importance of intrinsic factors in the motivation of faculty to teach 6 8 . Although academic institutions devote time and resources to extrinsic recognition of their rural and distributed faculty, there is limited literature to guide these efforts 9 , 10 . As a result, there is a risk that these initiatives might be ineffective or misperceived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work on the engagement of rural and distributed faculty has emphasized the importance of intrinsic factors in the motivation of faculty to teach 6 8 . Although academic institutions devote time and resources to extrinsic recognition of their rural and distributed faculty, there is limited literature to guide these efforts 9 , 10 . As a result, there is a risk that these initiatives might be ineffective or misperceived.…”
Section: Discussionmentioning
confidence: 99%
“…Other literature has also supported the importance of extrinsic motivators. A study examining willingness to teach among general practitioners in Germany found that engagement was related to intrinsic interest in teaching, but that fair compensation was also important 9 . A study of community preceptors in North Carolina found that monetary compensation was an important extrinsic motivator 10 .…”
Section: Introductionmentioning
confidence: 99%
“…This may be because in the German health care system, a primary care practice acts like a small business in the hands of the GP or a group of GPs. In our experience, many general practitioners want to share their knowledge, skills and experience as a GP with the next generation of medical students [ 26 ]. Our “GP learning stations” in a clinical setting offer this opportunity with a low threshold.…”
Section: Discussionmentioning
confidence: 99%
“…They request clear learning objectives and assessment criteria and wish for opportunities for professional development 54 . A questionnaire survey among German GPs identified the following most important facilitators: long‐term scheduling, availability of teaching materials and equate financial compensation; and barriers: time restraints and decreased productivity 55 …”
Section: Discussionmentioning
confidence: 99%